The Internal and external Rate of Return (IRR and ERR) Methods: A Look into Their Features and Relevance - Bhattarai, Baburam (Economic Journal of Nepal, 2006)
This paper describes the features and examines the context in which internal rate of return (IRR) and external rate of return (ERR) are appropriate. Side by side, it tries to bring into light some of the basic aspects of economic evaluation of engineering projects before the wider circle of economists and other development workers. Economic Journal of Nepal Vol.29(1) 2006 pp.30-37